In vivo Pirt-Marina voltage sensor imaging detects primary sensory neuron–specific voltage dynamics and neuronal plasticity changes - Yan Zhang; Hyeonwi Son; John Shannonhouse; Ruben Gomez; Eungyung Kim; Chih-Hsuan Ai; Man-Kyo Chung; Jelena Platisa; Vincent A. Pieribone; Yu Shin Kim (Proceedings of the National Academy of Sciences, 2025)
In vivo voltage imaging is a powerful tool for monitoring action potentials and dynamic electrical events in heterogeneous sensory neurons enabling the deciphering of rapid somatosensory information processing. Virus-driven expression of genetically encoded voltage indicator (GEVI) suffers from inconsistent expression levels and offers a limited time window for optimal voltage imaging. Here, we generated and characterized a knock-in mouse line with Pirt-driven expression of Marina, a positively tuned GEVI, in primary sensory neurons. Pirt-Marina mice enable optical reporting of touch, itch, and nociceptive sensations in vivo and distinct action potential patterns in the trigeminal and dorsal root ganglion neurons. Notably, Pirt-Marina mice display robust fluorescence signals in response to mechanical, thermal, or chemical stimuli, allowing visualization of transformations in sensory coding following inflammation and injury. This Pirt-Marina mouse line provides optical access to dynamic neuronal activity and plasticity in the peripheral nervous system (PNS) with high temporal accuracy, fidelity, and reliability.